Legal and Institutional Obstacles to Growth and Business in Russia - Buckberg, Elaine (IMF Policy Discussion Papers; Policy Discussion Paper, 1997)
Although financial stabilization has laid the foundation for growth, structural reform of the economy will determine whether Russia achieves sustained medium-term growth. The next step for Russia is to create an institutional and regulatory environment that fosters investment and promotes new private sector activity. This paper examines the most critical reforms for promoting private sector development: reforming the tax system, reducing red tape and bureaucratic corruption, strengthening the judicial system, and improving capital market infrastructure.